Marketing for Tourism / Third Edition - Holloway Christopher J; Robinson Chris (Longman, 1995)
An introduction to the general theory of marketing and its application in the various sectors of the travel and tourism industry. Preface, The Marketing Perspective, Marketing Planning, Marketing Research and Its Applications in Tourism, The Tourist Market, Tourism Product Policy, Pricing the Product, Marketing Communications, The Distribution System, Tourism Advertising, The Travel Brochure, Sales Promotion for Travel and Tourism, Direct Marketing: Theory and Practice, Public Relations and its Use in the Tourism, Marketing Control, Case Studies, Bibliography, Index.